Characterization and analysis of electrical trap related effects on the reliability of AlInN/GaN HEMTs. Issue 9 (August 2015) - Petitdidier, S.; Berthet, F.; Guhel, Y.; Trolet, J.L.; Mary, P.; Gaquière, C.; Boudart, B.
Abstract: This paper shows the influence of pre-existing electrical traps on the reliability of AlInN/GaN HEMTs by using simple methods. So, a kink effect has been highlighted by studying the impact of the illumination and the bias conditions on the electrical characteristics of the AlInN/GaN devices. Then, these devices have been electrically stressed for 216 h under three different bias conditions such as Off-state stress, On-state stress, and Negative Gate Bias (NGB) stress. All these electrical stresses induce a decrease in drain current and an increase in access resistance. However, the degradation of the drain current and the access resistances are more important after an On-state stress than an Off-state stress than a NGB stress. We have highlighted that the three different stresses induce more acceptor than donor traps in AlInN/GaN devices. The degradation of the electrical properties of stressed devices seems irreversible. Moreover, an evolution of the kink effect has been observed after the three ageing tests. To our knowledge, it is the first time that the impact of the pre-existing electrical traps on the degradation mechanism induced by On-state, Off-state and NGB stresses is carried out on AlInN/GaN devices. Highlights: AlInN/GaN transistors are candidates for high power applications. AlInN/GaN transistors are candidates for high frequencies applications. Acceptor and donor traps induced by On-state, Off-state and NGB stress. Influence of pre-existing traps on AlInN/GaN HEMTs reliability. Influence of stress parameters on AlInN/GaN HEMTs reliability.